Utilization of Facebook as a Media for Creativity and Actualization for Students at SMKN 1 Nusawungu - Prasetyo, Purcahyono Hari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine the extent to which the social network Facebook is used as a means to express creativity and apply it in the context of learning creative products and entrepreneurship, as well as extracurricular activities. The research method applied is a qualitative phenomenological approach, examining phenomena that emerge among Nusawungu Vocational School students regarding the use of social media as a medium for actualization and expression of creativity. The results obtained from this research found various activities carried out by students related to the use of Facebook as a creative forum and source of information among students. Such as using Facebook to share photos, videos, exchange ideas in extracurricular activities. As a promotional medium for entrepreneurial products